Abnormal vocal cord movement in patients with and without airway obstruction and asthma symptoms. Issue 2 (24th October 2016) - Low, K.; Ruane, L.; Uddin, N.; Finlay, P.; Lau, K. K.; Hamza, K.; Holmes, P. W.; Hamilton, G.; Bardin, P. G.
Summary: Background: Abnormal vocal cord movements can cause laryngeal extrathoracic airway obstruction (often called vocal cord dysfunction – VCD) leading to asthma‐like symptoms. These aberrant movements are characteristically present during inspiration and termed paradoxical vocal cord movement (PVCM). We have reported PVCM in up to 40% of severe asthmatics, but it is not known if PVCM is detectable in all patients with asthma‐like symptoms and if the condition is more often associated with abnormal lung function. Objective: We hypothesized that PVCM is frequently associated with asthma symptoms accompanied by airflow limitation. Studies examined whether PVCM is solely linked to experiencing asthma symptoms, or if PVCM is related to airflow limitation and/or other disease characteristics. Methods: Patients with asthma symptoms were recruited from general practice and severe asthma clinics ( n = 155). Pulmonary function measurements were conducted, asthma control and Nijmegen (dysfunctional breathing) questionnaires were administered and skin prick testing was carried out. PVCM was quantified using dynamic 320‐slice computerized tomography of the larynx. Groups were divided into patients with FEV1 ≥ 80% predicted or FEV1 < 80% predicted and FEV1 /FVC < 0.7. ATS/ERS definitions of severity were also applied and evaluated. Detection of PVCM in the groups was compared and analyses performed to identify features associated with PVCM. Results: Overall ( n = 155), PVCM was detected in 42 cases (27.1%). Patients with FEV1 < 80% predicted had PVCM more often (25/68, 36.8%) than individuals with normal spirometry (17/87, 19.5%; P = 0.016). PVCM was associated with older age ( P = 0.003) and with Nijmegen scores > 20 ( P = 0.04). Patients with FEV1 < 80% predicted plus Nijmegen scores > 20 were more likely to have PVCM (OR = 9.3, P = 0.02). Conclusions and Clinical Relevance: Paradoxical vocal cord movement is more often associated with asthma symptoms accompanied by airflow limitation and dysfunctional breathing. Further studies are needed to determine whether PVCM is induced by dysfunctional breathing practices and/or airway obstruction. How PVCM links with symptomatic asthma and VCD also requires evaluation.